Application of Room Temperature Ionic Liquids in Electrochemical Sensors and Biosensors - Faridbod, Farnoush; Ganjali, Mohammad Reza; Norouzi, Parviz; Riahi, Siavash; Rashedi, Hamid (IntechOpen, 2011)
None